Promoting Creativity for younger school age children in arts field subject integration - Garjāne, Beatrise; Kļave, Ande (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article reveals the main lines of identifying the nature of creativity, highlighting the importance of creativity in education in general and arts subjects, justifying the need for integration of these items. This paper analyses the international experience in arts education and cultural education the author of the article to dis; the framework of study reveals the situation in Latvia. The study results prompted cuss arts subjects integration educational opportunities associated with industry experts and arts teacher beliefs.